Sofrimento psíquico em estudantes universitários: prevalência e determinantes dos Transtornos Mentais Comuns (TMC) em discentes de uma universidade pública federal - Rienzo, Israel Roberto de (Universidade Federal de São Carlos, 2025)
Psychological distress, influenced by various sociopolitical and institutional changes that impact student persistence and well-being, has become a growing challenge. The objective of this study was to calculate the prevalence of psychological distress and depression, as well as to correlate social and clinical markers with these phenomena among students at a federal public university. This quantitative, cross-sectional, and descriptive study was conducted with 174 undergraduate and graduate students at the Federal University of São Carlos (UFSCar), São Carlos campus. The prevalence of psychological distress was 77.9% and that of depression was 56.6% — measured by the Self-Reporting Questionnaire (SRQ-20) and Patient Health Questionnaire (PHQ-9), respectively — while the combined prevalence of both conditions was 78.2%. Age group and prior health history were directly related to these phenomena. Therefore, this study contributes to the development of health promotion strategies that consider the identified social markers.
Psychological distress in university students: prevalence and determinants of Common Mental Disorders (CMD) in students of a federal public university
Keywords: Epidemiologia; Estudos de prevalência; Universidades; Saúde do estudante; Sofrimento psicológico; Epidemiology; Cross-sectional studies; Universities; Student health; Psychological distress; CIENCIAS DA SAUDE::SAUDE COLETIVA; 3. Saúde e Bem-Estar